A filosofia nos livros didáticos do novo ensino médio - Santos, Silvia Regina Macário dos (2024)
The cartography Philosophy in Textbooks of the New High School aims to answer the question What is Philosophy in the books of Human and Applied Social Sciences that appear in the National Textbook Plan (PNLD) of this new High School?, but for this I start from belief that the teaching of philosophy in high school should be a curricular component that seeks to create concepts, as thought by Deleuze and Guattari in What is philosophy? (1992), thus exercising a pedagogy of the concept, emphasizing Sílvio Gallo's proposal, which is to transform philosophy classes into a laboratory for the experience of thinking through the “concept workshop”. The cartography is divided into three plateaus. The first plateau consists of bibliographical research and theoretical study that justify the teaching of philosophy as an activity of creating concepts, as initially thought by Deleuze and Guattari in What is philosophy? (1992) and defended by Sílvio Gallo. In the second plateau I make a brief discussion about the new National Common Curricular Base (BNCC - Secondary Education), addressing the chronology of the implementation of the new Secondary Education and bringing points of view about it, mainly with regard to the philosophy curricular component. In the third and final plateau I bring the product, the result of this cartography: an analysis of the textbooks that appear in the PNLD. This analysis is based on philosophy as the creation of concepts and geophilosophy. The analysis of the books did not follow a common pattern of positive or negative thinking, as I believe, within a view of difference, it is always possible to create movements, exchange the or for and, and, and (the stuttering), escape, produce new meanings and deterritorialize. I make movements of captures and ruptures, simultaneously, and draw lines and cartographies. Breaking models. It is a positive and negative analysis, thinking about a creative stutter, thinking about books as plateaus and resonances, observing their signifiers and meanings, asking them what their dominant meanings and subjectivities are. Seeking answers that produce war machines, resistance outside the system, through affections, intensities, experiences and experiments. And for this, I believe that the teacher needs to create.